The Association of Transformational Leadership on Safety Practices Among Nurses: The Mediating Role of Patient Safety Culture - Hamdan M.; Jaaffar A.H.; Khraisat O.; Issa M.R.; Jarrar M. (Dove Medical Press Ltd, 2025)
Background: To ensure best possible patient outcomes, patient safety is a major component of healthcare delivery system that needs to be prioritized. Safety practices among nurses are essential to maintain patient safety, especially the practices of medication administration, handover, patient falls and unplanned extubations prevention. Purpose: To investigate the mediating effect of patient safety culture between the relationship of transformational leadership and safety practices among nurses. Methods: The data in this cross-sectional study were gathered from a survey targeted clinical nurses using a random sampling technique. The study was conducted in a medical city in Saudi Arabia, and two hundred nurses were surveyed. The Multifactor Leadership, Hospital Survey on Patient Safety Culture, and Nursing Safety Practice questionnaires were used in the study. Results: The results revealed significant positive associations between transformational leadership, patient safety culture, and nursing safety practices. Moreover, patient safety culture mediates the association between transformational leadership and safety practices among nurses. Conclusion: Enhancing transformational leadership capabilities among nurse managers should be considered in order to improve nursing safety practices. Additionally, patient safety culture should be measured and improved periodically to ensure better nursing safety practices. ? 2024 Hamdan et al.